Morfological Awareness of Students English Language Program of Universitas Islam Riau Pekanbaru: An Analysis Study - Rugaiyah, R (CV. Inara, 2021)
This study is aimed to investigate the students’ morphological awareness which is employed by the third semester of English students FKIP Universitas Islam Riau Pekanbaru Riau, Indonesia.This study is the qualitative design namely case study. The instrument of this study was documentation or the scrips of the students in the final examination result in the academic year 2019-2020. In this case, the researcher has analyzed the data using the Cresswell method. The result of this study found that some of the students still have a problem in using derivational affixes such as in changing the classes of words from verb to noun, noun to adjective, adjective to a verb, adjective to an adverb